FOSTERING THE STUDENTS’ COURAGE IN ENGLISH TENSES MASTERY THROUGH THE SMART FINGERS TECHNIQUE - Nova Adi Kurniawan (Program Studi Pendidikan Bahasa Inggris, 2022)
Courage becomes one of requirements the students should have in language proficiency. This research is to figure out the students’ courage in learning English tenses by using the smart fingers and to find the effectiveness of the smart fingers to foster the students’ courage. This study is experimental research by pre-experimental design. It only uses one group pretest and posttest. There were 25 students of Semester 1 of Syaria Economic Study Program joining the research. It was held on September to October 2022. The data was expanded by using tests of English tenses mastery, pre-test and posttest. The data were then analyzed using t-test through the use of Ms. Excell. The findings revealed that students’ mean score of pre-tests is 70,36 and 74,64 for posttest. The result of t-test is t-Test = Sig. 0,0037171 < Sig. 0,05, and Ha is accepted. Accordingly, the smart fingers technique is effective to be used in teaching English tenses by significance score of 0,0037171.